Effect of Agaricus bisporus enriched diet on growth, hematology, and immune protection in Clarias gariepinus against Flavobacterium columnare. Issue 73 (February 2018) - Harikrishnan, Ramasamy; Naafar, Adil; Musthafa, Mohamed Saiyad; Ahamed, Anis; Arif, Ibrahim A.; Balasundaram, Chellam
Abstract: The purpose of the present study was to find out the effect of dietary enriched button mushroom, Agaricus bisporus at 1%, 5%, and 10% levels on growth performance, hematology, nonspecific immune responses, and disease resistance in catfish, Clarias gariepinus against Flavobacterium columnare for a period of four weeks. The percentage weight gain and specific growth rate (SGR) were higher in the infected fish fed with 5% A. bisporus enriched diet than with 1% and 10% diets. The red blood cell (RBC), white blood cell (WBC), hematocrit (PCV), and haemoglobin (Hb) values are similar (p > .05) among the experimental groups at the end of fourth week. The phagocytic activity, complement activity, and lysozyme activity were significantly enhanced in the infected fish fed with 5% A. bisporus diet during the experimental period; however, it was significantly enhanced with 10% A. bisporus enriched diet only on weeks 2 and 4. On the other hand, the respiratory burst (RB) activity increased significantly in the infected fish fed with 5% and 10% A. bisporus enriched diets. When fed with 5% A. bisporus diet the cumulative mortality was very low (10%), followed by a high survival rate (89%) in the infected fish; nevertheless, the cumulative mortality was 25% and 20% while it was 74% and 79% when fed with 1% and 10% enriched diets. The present study recommends a dietary supplement of A. bisporus at 5% or 10% level to achieve better growth without side effect, and enhance the nonspecific immune system that prevent mortalities from F. columnare infection in C. gariepinus . Highlights: RBC, WBC, PCV, Hb values are similar (p > .05) among the experimental groups. Phagocytic, complement, and lysozyme activities significantly enhanced with 5% A. bisporus diet. Respiratory burst activity significantly enhanced in fish fed with 5% and 10% A. bisporus diets. Low (10%) cumulative mortality and high (89%) survival rate obtained in fish fed with 5% A. bisporus diet.